Does gender matter for firm performance? Evidence from Eastern Europe and Central Asia - Sabarwal, Shwetlena; Terrell, Katherine (Bonn, 2008)
"Using 2005 firm level data for 26 ECA countries, this paper estimates performance gaps between male- and female-owned businesses, while controlling for their location by industry and country. We find that female entrepreneurs have significantly smaller scale of operations (as measured by sales revenues) and are less efficient in terms of Total Factor Productivity (TFP), although this difference is very small. However, they generate the same amount of profit per unit of revenue as men. We find that while both male and female entrepreneurs in ECA are sub-optimally small, women's returns to scale are significantly larger than men's implying that they would gain more from increasing their scale. We argue that the main reasons for the sub-optimal size of female-owned firms are that they are both capital constrained and concentrated in industries with small firms."